Situational analysis on the antimicrobial resistance patterns among bacterial isolates from diseased small animals, livestock and wildlife - Haulisah, Nurul Asyiqin (2021)
Antimicrobial resistance (AMR) is a global threat of immense significance to the health of animals and humans. While there is an abundance of reports on AMR among clinical isolates from humans, information regarding the patterns of resistance among clinical isolates from animals is scarce. Hence a situational analysis of AMR among the clinical cases received at a veterinary diagnostic laboratory was performed to describe the pattern of resistance demonstrated by clinical isolates. Specifically, this study describes the AMR pattern of clinically important pathogens from pets and livestock using retrospective laboratory data between 2015 and 2017, and determine the resistance patterns of selected pathogens of public health significance from domestic and wildlife between 2018 and 2019. In diseased pets, Escherichia coli was the most commonly isolated (n=101, 13%) bacteria. Additionally, E. coli from the pets was highly resistant to amoxicillin (73.2%) and cephalexin (66.3%). Moreover, more than 75% of isolates from diseased pets were multi-drug resistant (MDR). Isolates from cats appeared to have higher level of resistance to multiple antibiotics compared to those from dogs. While in diseased livestock, Escherichia coli was the most commonly isolated (n=185, 26%) bacteria, and (>77%) were resistant to neomycin and streptomycin. Moreover, more than 76% of isolates from livestock were MDR. In general, isolates from non-ruminants have a higher level of resistance to multiple antibiotics compared to ruminants. In conclusion, this study has highlighted the trends and level of AMR among clinical isolates from pets and livestock based on routine antibiotic therapies. This study also discovered the trends of resistance among clinical isolates to those antibiotics of public health significance using the scope of testing as described by the national integrated surveillance for AMR.